Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Kelurahan Bojong Rawalumbu - Salsabila Putri Adhisty; Zahara Tussoleha Rony; Rycha Kuwara Sari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of the work environment and work motivation on employee performance at the Bojong Rawalumbu sub-district office. The type of research used in this research is quantitative research. The sampling technique used a saturated sampling technique through a questionnaire created via Google Form with the criteria of all 58 Bojong Rawalumbu sub-district office employees. The data analysis method uses multiple linear regression. The data was processed using IBM SPSS Statistics 23. The results of this study show that (1) the work environment has a significant effect on employee performance at the Bojong Rawalumbu sub-district office, (2) Work motivation has a significant effect on employee performance at the Bojong Rawalumbu sub-district office and (3) The work environment and work motivation simultaneously influence employee performance at the Bojong Rawalumbu sub-district office.